Pelatihan Teknik Merangkai Hantaran Busana Lingerie Bagi Pengusaha Muda - Romadhona Chusna Tsani; Arina Haq (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2025)
Training on techniques for assembling lingerie clothing gifts is one of the training in assembling gifts given to young entrepreneurs at community service activities at SKB Ungaran. This training aims to provide skills to young entrepreneurs who are starting a business in the field of delivery manufacturing. The skills provided include training in basic techniques for folding gifts, assembling lingerie gifts, creating gift accessories. The training method used is the Service Learning method, where the trainer will provide examples in each training, which will then be followed by the training participants. Indicators of the success of training in techniques for assembling lingerie delivery for young entrepreneurs can be seen from four aspects, namely 1) Accuracy in implementing the training; 2) Percentage of attendance of training participants; 3) The enthusiasm of the training participants; and 4) Training results. From these four indicators of success, it is known that the training was carried out according to the specified time, The attendance of training participants reached 90% which can be concluded that the participants were enthusiastic during the training. This training activity also produced a product in the form of a set of lingerie and accessories. The results of interviews with training participants also show that this training can broaden participants' insight and skills in the field of delivery